Perspectives on the Values in University Administration :: Reflection on Empiricism Through Critical Paradigm - Christy, Nisa Novia Avien; Wu, Ming-Chang; Wibowo, Radna Andi; Dwiantari, Scorina (JURNAL ILMIAH EDUNOMIKA, 2025)
The current educational environment is characterized by a high level of competitive pressure, which is the result of meritocratic policies and the multifaceted resources available. Universities are encouraged to use measurable, often instantaneous, accomplishments to demonstrate their self-accreditation. Consequently, the university administration strives to establish a mundane institutional reputation by focusing on quantitative but superficial metrics, including project grants, apparatus upgrades, and paper publication. In order to candidly envision the future of institutions and engage in a more in-depth discussion of the fundamental objectives of university education, there is a limited amount of reflection on the values of current university development. Consequently, this investigation employs literature analysis approaches to synthesize the subsequent issues: (1) the obstacles to empiricism and performanceism in university environments, (2) the reflection of administration values in contemporary universities, and (3) the proposed strategies for enhancing the fundamental values of university administration.